Causative Factors of Chronic Kidney Disease in Patiens with Hemodialysis Therapy - Rahman, Shahrul; Santika, Kasih (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Chronic kidney disease (CKD) is a pathological process with various etiologies, causing decreased kidney function progressively and irreversibly. The prevalence of CKD in the last ten years has increased. Causative factors of CKD vary highly in each countries around the world. Hemodialysis is still the primary kidney therapy besides peritoneal dialysis and kidney transplantation. This study aims to discover the causative factors of chronic kidney disease in patients with hemodialysis therapy at the Medan Rasyida Kidney Specialty Hospital in 2019. The design of this research is a descriptive method, the respondents were 307 chronic kidney disease patients with hemodialysis therapy taken by total sampling. The most common factors causing chronic kidney disease in patients with hemodialysis therapy were hypertension (59.6%), diabetes mellitus (32.2%), obstructive nephropathy (2.6%), and gout nephropathy (2.3%), polycystic kidney (2.0%) and glomerulonephritis (1.3%). Hypertension is the most common cause of CKD in Medan Rasyida Kidney Hospital in 2019.